Analisis Ketidakpuasan Kerja Karyawan Organik & Non-Organik Pada PT. Pupuk Kujang Cikampek - Rohman, Andrian Fatur; Chaerudin, Chaerudin (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
The need for human resources requires companies to operate regularly. Manage and utilize existing employees to assist in achieving organizational goals. One so lution is to pay attention to the job satisfaction of each employee. This research is descriptive and uses quantitative methods. The subjects of this examination were 81 permanent employees and 185 non-permanent employees at PT. Pupuk Kujang, the total sample size was 266 people. The topic of this research is job dissatisfaction among contract and permanent employees. Based on the analysis above, 81 organic employees at PT. Pupuk Kujang uses Excel, the results of the TK O (Organic employee dissatisfaction survey showed that 28% were dissatisfied due to many reasons, one of which was a large workload. Based on the analysis above, 185 contract employees at PT. Pupuk Kujang uses Excel, the results of an on- organic employee dissatisfaction survey were 29% who felt dissatisfied due to several reasons, one of which was related to the compensation they received. In this research, quantitative data is in the for mof information collected from survey participants. The data sources used in this research are primary data and secondary data. Primary data is data collected by researchers or directly from research sources through in - depth interview methods, while secondary data is collected by researchers or collected from various available sources such as documents and questionnaires related to research. The data collection methods used in this research are (1) observation, (2) in -depth interviews and (3) documents, while the data analysis methods used are (1) data collection, (2) distributing questionnaires, (3) data processing.     Keywords: HR, dissatisfaction, PT. Pupuk Kujang, permanent employees, contract employees.